2020
DOI: 10.31222/osf.io/cm5v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interdisciplinarity Can Aid the Spread of Better Methods Between Scientific Communities

Abstract: Why do bad methods persist in some academic disciplines, even when they have been clearly rejected in others? What factors allow good methodological advances to spread across disciplines? In this paper, we investigate some key features determining the success and failure of methodological spread between the sciences. We introduce a model that considers factors like methodological competence and reviewer bias towards one's own methods. We show how self-preferential biases can protect poor methodology within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The past 20 years have seen a growing number of reptile home range studies and continued reliance on traditional but outdated methods, Kernel Density Estimations (KDEs) and Minimum Convex Polygons (MCPs), for home range and space-use estimations, despite more appropriate available methods. Scientific conventions can be slow to shift, and often require substantial interdisciplinary research to move towards better alternatives (Smaldino & O’Connor, 2020). We appeal to researchers focusing on reptiles to engage with quantitative ecologists to ease the uptake of more complex and appropriate statistical methods and thus maximize the value of hard-won field data.…”
Section: Resultsmentioning
confidence: 99%
“…The past 20 years have seen a growing number of reptile home range studies and continued reliance on traditional but outdated methods, Kernel Density Estimations (KDEs) and Minimum Convex Polygons (MCPs), for home range and space-use estimations, despite more appropriate available methods. Scientific conventions can be slow to shift, and often require substantial interdisciplinary research to move towards better alternatives (Smaldino & O’Connor, 2020). We appeal to researchers focusing on reptiles to engage with quantitative ecologists to ease the uptake of more complex and appropriate statistical methods and thus maximize the value of hard-won field data.…”
Section: Resultsmentioning
confidence: 99%
“…Yet implementations of PROCESS-style models are often reported with little awareness, let alone critical reflection of the underlying assumptions. We may thus be confronted with normative methods that have been selected to further publication instead of discovery (Smaldino & McElreath, 2016) , and such suboptimal methods can be quite persistent, in particular if there is little interdisciplinary exchange (Smaldino & O'Connor, 2020) . This unfortunate situation can occur without any ill intention on the part of 13 As a result, many PROCESS models are observationally equivalent.…”
Section: Conclusion: Rethinking the Research Processmentioning
confidence: 99%
“…Personality psychology can benefit from the input of other psychological subdisciplines and other scientific disciplines -and also vice versa. Increasing collaborative efforts between disciplines can yield several beneficial outcomes, such as gaining new knowledge and insights, expanding traditional ways of thinking and working, serving a larger and more diverse community, counteracting isolated research endeavors, and mitigating the problematic use of methods (Devezer et al, 2019;Green & Johnson, 2015;Smaldino & O'Connor, 2020). However, to be truly successful, personality science not only needs to be rigorous, credible, and cumulative, it will also need to be open, collaborative, and inclusive.…”
Section: Expanding the Fieldmentioning
confidence: 99%
“…In another computational experiment, Hong and Page (2004) showed that, because of their diversity in problem-solving, randomly selected problem-solving teams could outperform teams of best-performers. In a further mathematical model, Smaldino and O'Connor (2020) demonstrated that methodological improvements could be spurred by incorporating feedback from outside disciplines (see also Expansion of the Field above). Taken together, diversity in research approaches could buffer shortcomings of single research strategies, increase the competent use of good methods, expand the realm of questions asked, accelerate scientific discovery, and help arrive at more reproducible and "true" findings more efficiently.…”
Section: Expanding Diversities In the Fieldmentioning
confidence: 99%